The truth about twinkie pie - Yet, Kat (SCHOLASTIC, 2015)
The truth about twinkie pie There's something about asking for impossible Things. For one little second, they feel Possible. Take two sisters making it on their own: brainy twelve-year-old GiGi and junior-high-dropout-turned-jairrtylist DiDi. Add a million dollars in prize money from a national cooking contest and a move from the trailer parts of South Carolina to the North Shore of Long Island. Mix in a fancy new school, new friends and enemies, a first crush, and a generous sprinkling of family secrets.